Pendidikan SEMAIZIBANG (Semai Gizi Seimbang) Berfokus Pada Pengetahuan, Sikap Dan Pola Makan Bagi Siswa Sekolah Menengah Pertama di Kabupaten Lombok Timur: The SEMAIZIBANG (Sowing Balance Nutrition) Education on Knowledge, Attitude, and Diets for Students of Junior High School in East Lombok Regency - Fitri Amelia; Lalu Khairul Abdi; I Gde Narda Widiada; Lalu Juntra Utama; Egy Sunanda Putra; Lina Yunita (Amerta Nutrition, 2026)
Background: According to Indonesian Health Survey in 2023, the prevalence of stunting among adolescents aged 13-15 years was 17.5%, with severe cases, overweight, and underweight reaching 6.6%, 16.2%, and 7.6%, respectively. To address this health condition, there is a need to effectively improve knowledge and attitudes by maintaining a balanced diet through the provision of nutrition education using the SEMAIZIBANG (Showing Balanced Nutrition) card game.   Objectives: This research aimed to determine the difference in nutrition education using the SEMAIZIBANG card game media with lectures on improving knowledge, attitudes, and balanced nutrition diets for junior high school students. Methods: The quasi-experimental research was conducted using a pretest and posttest design, with a total of 48 participants selected for each group through the Slovin formula. Data collection was performed using validated knowledge and attitude questionnaires, alongside Food Frequency Questionnaire (FFQ) form. The intervention group was given nutrition education through the SEMAIZIBANG card game, while the control received a lecture method, with both groups subjected to 8 treatments. The data obtained were tested through paired and independent sample t-tests. Results: The results showed that there was a significant increase in knowledge and attitudes in education with SEMAIZIBANG media (p-value 0.077), but not in dietary patterns. The difference test between the two groups showed significant variation in knowledge and attitudes but not in dietary patterns (p-value 0.379). Conclusions: This research shows that nutrition education through the SEMAIZIBANG card game or lectures significantly improves students knowledge and attitudes. However, the dietary patterns are not affected due to the short intervention duration and limited assessment.